Place of anti-EGFR therapy in older patients with metastatic colorectal cancer in 2020. Issue 8 (November 2020) - Gilabert, Marine; Ries, Pauline; Chanez, Brice; Triby, Simon; Francois, Eric; Lièvre, Astrid; Rousseau, Frederique
Abstract: Almost half of the new cases of colorectal cancer concern patients aged ≥70 years. However, very few clinical trials have specifically included older patients. As a consequence, the treatment of these patients is controversial because the balance between clinical benefits and toxicities remains uncertain. In patients without comorbidities and with an ECOG performance score of 0–1, treatment indications are similar to those of younger patients. For frail patients, chemotherapy is possible, but a comprehensive geriatric assessment is recommended. Anti-EGFR (epidermal growth factor receptor) therapy is indicated either in combination with chemotherapy in the first-line or second-line setting or as monotherapy in the third-line setting (i.e., after failure of chemotherapy). For fit older patients, clinical trials that compared chemotherapy alone with doublet chemotherapy plus anti-EGFR in either first-line or second-line setting suggested that age is not an absolute contraindication for the use of this regimen. In frail patients, anti-EGFR monotherapy in the first-line, second-line or third-line setting has shown feasibility and antitumor activity and had mainly cutaneous toxicities that were easily managed. In any case, administration of treatment must be very cautious in older patients and the treatment dose needs to be adapted according to comorbidities.